IMPACT OF SCHEMES ON THE FORMATION OF FINANCIAL STATEMENTS IN THE PUBLIC SECTOR - Dimitrijević, Ljiljana; Eremić-Đođić, Jelica M; Radojičić, Dušan (Poslovna ekonomija, 2024)
USERS OF PUBLIC FUNDS ARE REQUIRED BY LAW TO PREPARE FINANCIAL REPORTS, WHICH PROVIDE INFORMATION ON THE FINANCIAL POSITION, RESULTS AND CHANGES NEEDED BY MANAGEMENT IN MAKING THEIR ECONOMIC DECISIONS. THE GOVERNMENT OF THE REPUBLIC OF SERBIA CONTINUED WITH THE PUBLIC FINANCIAL MANAGEMENT REFORM PROGRAM FOR THE PERIOD 2021-2025, WHICH AMONG THE OTHER SCOPE AND A SPECIAL OBJECTIVE - IMPROVEMENT OF ACCOUNTING IN THE PUBLIC SECTOR BY APPLICATION OF INTERNATIONAL PUBLIC SECTOR ACCOUNTING STANDARDS (IPSAS). THESE STANDARDS WILL ACHIEVE GREATER TRANSPARENCY OF REPORTING, BECAUSE WE WILL GET INFORMATION ON THE ASSETS, LIABILITIES, NET ASSETS, INCOME AND EXPENDITURES OF THE ENTIRE PUBLIC SECTOR BY USING THE ACCOUNTING BASIS. THE STRATEGIC GOAL OF ACCOUNTING IN THE PUBLIC SECTOR OF THE REPUBLIC OF SERBIA IS THE FULL IMPLEMENTATION OF IPSAS BY 2034. In order to fulfill this goal, we need to unify the accounting software of the budget users, the main books, auxiliaries to easier business, consolidation. AUTOMATION OF POSTINGS IN THE TREASURY'S GENERAL BOOK AND COMPILATION OF FINANCIAL REPORTS. WE WILL ACHIEVE MORE RELIABLE AND OBJECTIVE FINANCIAL REPORTING IF WE IMPROVE INFORMATION TECHNOLOGY, IN A WAY TO INCORPORATE CRIMINAL SCHEMES WHICH WE WILL DISCOVER ERRORS WELL AND SUFFICIENTLY PERSPECTIVE: INTENTIONAL OR UNINTENTIONAL AND CONTRIBUTE TO MORE ECONOMIC, EFFICIENT AND EFFICIENT MANAGEMENT OF PUBLIC FUNDS. IN THIS, A YOUNG SCIENTIFIC DISCIPLINE WILL HELP US WITH MANY SPECIFICITIES - FORENSIC AUDIT. THE GOVERNMENT AND ITS INSTITUTIONS ARE INTERESTED IN INFORMATION ON THE EFFICIENCY OF USING ALLOCATED RESOURCES FOR DEFINING FISCAL POLICY, KEEPING STATISTICAL RECORDS ON NATIONAL INCOME AND OTHER DATA NECESSARY FOR LEADING THE POLICY OF DEVELOPMENT OF THE NATIONAL ECONOMY.
Keywords: schemes, audit, finanscial reporting, public sector, Accounting Standards, forensic audit